Effect of red light on the synthesis of wound ethylene in etiolated pea shoots - Rohwer, Frauke; Schierle, Joseph (Journal of plant physiology, 1984)
Summary: Apical segments from 7-day-old etiolated pea seedlings (Pisum sativum L. cv. Vorbote) produced 3 to 4 nl C2H4 h-1g-1 f.w. during the first 5 hours after excision. This formation of wound ethylene was due to a sharp increase of ACC concentration in the segments after exision. A 15 min red light pulse (approx. 0.22 W m-2) applied 3 hours before excision prevented the increase of ACC and inhibited wound ethylene formation. The lower ACC level was not caused by a higher rate of metabolism of ACC to MACC and also the capacity for the conversion of ACC to ethylene was not affected by the red light pulse. We therefore relate the lower ethylene formation after red light to an inhibition of wound ACC formation. The red light effect on wound ethylene production was reversible by far red light, so it can be explained as a phytochrome effect. Exogenous ethylene had a similar effect on the synthesis of wound ethylene as red light. Possible relations between these two effects are discussed.
Gesehen am 09.04.2018